Mobile applications in clinical practice: What is needed in the pharmacy scenario? - Elnaem, Mohamed Hassan Abdelaziz; Jamshed, Shazia Qasim (Archives of Global Professionals, 2017)
Pharmacy informatics is demonstrated to have a positive effect on pharmacy practice. The incorporation of pharmacy informatics in academic programs is a common feature in the pharmacy curriculum. This work aims to provide an overview of the current and potential role of mobile applications (apps) in pharmacy education and practice. Mobile apps are the most common informatics tools used by medical and pharmacy practitioners as well as students. Both students and practitioners have overall positive perceptions toward using mobile apps in their daily clinical training and practice although the fact that the number of pharmacy apps is still small relatively in comparison with other medical-related apps. There are many potential roles for mobile apps in pharmacy practice and education. The future efforts of educational uses of mobile apps in pharmacy should target playing a role in the provision of customized tools for clinical pharmacy education.